2016
DOI: 10.1186/s40066-016-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Shallow wells, the untapped resource with a potential to improve agriculture and food security in southern Mali

Abstract: Background: Excessive rainwater during the rainy season and lack of water in the dry season have been challenging the agricultural productivity and food security for rural communities in southern Mali. Various soil and water conservation practices were implemented in the past to improve crop yields and income, and reverse the effect of land degradation. However, none of these efforts looked into the potential use of shallow wells at a spatial scale to improve the agricultural productivity and hence the food se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Environmental factors (land use and land cover, distance to urban/ rural areas) and economic factors (distance to the road, slope, distance to river, population density) were sourced from the Malian national GIS database available at the Institute of Rulale Economy (IER). Groundwater level data was sourced from previously georeferenced databases of Birhanu and Tabo (2016) and the spatial records of IWMI (2019). The collected spatial data at different scales were brought together using GIS software and re-scaled to make the output at a district level.…”
Section: Data and Data Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Environmental factors (land use and land cover, distance to urban/ rural areas) and economic factors (distance to the road, slope, distance to river, population density) were sourced from the Malian national GIS database available at the Institute of Rulale Economy (IER). Groundwater level data was sourced from previously georeferenced databases of Birhanu and Tabo (2016) and the spatial records of IWMI (2019). The collected spatial data at different scales were brought together using GIS software and re-scaled to make the output at a district level.…”
Section: Data and Data Sourcementioning
confidence: 99%
“…The vegetable gardens, though limited in scope, allow diversification of food in the household, leading to an increased household income. Traditional irrigation is practiced using shallow wells that have depths ranging from 6.5 to 14.5 meters (Birhanu and Tabo, 2016). A recently conducted survey on water availability and access in rural Mali revealed that while 39% of rural Malians always lack water, periodic water shortages are experienced by the majority of communities (61%) (Sanogo et al, 2021) sometimes or the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Average bulk density is 1.5 g•cm 3 at 0 -20 cm soil horizon. These soils are inherently fragile with weak water retention capacity and poor in plant nutrients [12]. Soil pH varied from moderately acid (pH 2 O = 6.5) to acid (pH 2 O = 5.5), Organic Carbon (5 -6 g•kg −1 ), Nitrogen (<0.5 g•kg −1 ), available P (<0.07 g•kg −1 ), exchangeable K (<72 mg•kg −1 ), Cation Exchange Capacity (CEC) (4 -6 cmol•kg −1 ) and a base saturation ratio 75%.…”
Section: Study Sitesmentioning
confidence: 99%
“…[11] concluded that 44% of farmer's agricultural incomes losses are due to soil depletion which is a major factor influencing food security in the area and finally the economy of the country since it affects the main rainfed staple crop. According to [12], the major staple crops grown in southern Mali are millet (Pennisetum glaucum (L.) R. Br.…”
Section: Introductionmentioning
confidence: 99%